2015
DOI: 10.1038/ncomms9717
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin response factors regulate PIN-FORMED auxin transporters

Abstract: Auxin and cytokinin are key endogenous regulators of plant development. Although cytokinin-mediated modulation of auxin distribution is a developmentally crucial hormonal interaction, its molecular basis is largely unknown. Here we show a direct regulatory link between cytokinin signalling and the auxin transport machinery uncovering a mechanistic framework for cytokinin-auxin cross-talk. We show that the CYTOKININ RESPONSE FACTORS (CRFs), transcription factors downstream of cytokinin perception, transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 58 publications
3
79
0
Order By: Relevance
“…2009; Bishopp et al, 2011;Šimášková et al, 2015). Together our data suggest that YUC1 and PIN7 expression overlap with peak cytokinin signaling in the subapical medial tissue of the gynoecial primordium, and that cytokinin can promote medial auxin biosynthesis in, and PIN7-mediated auxin efflux from, this domain.…”
Section: Cytokinin Promotes Auxin Biosynthesis Gene Activity and Regumentioning
confidence: 59%
See 1 more Smart Citation
“…2009; Bishopp et al, 2011;Šimášková et al, 2015). Together our data suggest that YUC1 and PIN7 expression overlap with peak cytokinin signaling in the subapical medial tissue of the gynoecial primordium, and that cytokinin can promote medial auxin biosynthesis in, and PIN7-mediated auxin efflux from, this domain.…”
Section: Cytokinin Promotes Auxin Biosynthesis Gene Activity and Regumentioning
confidence: 59%
“…In roots, cytokinin signaling can regulate the expression of several YUC auxin biosynthesis genes (Jones et al, 2010;Di et al, 2016), and PIN1, PIN3, and PIN7 auxin efflux carriers (Dello Ioio et al, 2008;Ruzicka et al, 2009;Bishopp et al, 2011;Šimášková et al, 2015). We and others have previously shown that PIN1, PIN3, and PIN7 translational reporters are expressed in tissue-specific patterns in early stage gynoecial primordia (Larsson et al, 2014;Moubayidin and Ostergaard, 2014).…”
Section: Cytokinin Promotes Auxin Biosynthesis Gene Activity and Regumentioning
confidence: 96%
“…LR numbers of both crf2,5,6 and crf3,5,6 triple mutants were reduced compared with the wild type (Raines et al, 2016). Loss-offunction mutations in CRF2 or CRF3 or both CRF3 and CRF6 or CRF2, CRF3, and CRF6 caused reductions in root length, root meristem size, and LRP density, whereas overexpression of CRF2 or CRF3 or CRF6 enhanced LRP density ( Simá sková et al, 2015). In addition, multiple mutations in CRFs result in larger rosettes, delayed leaf senescence, and shorter hypocotyls in etiolated seedlings (Raines et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…This study demonstrated that CRF2 and CRF3 play an important role during LR development in Arabidopsis and also integrate the cold signal into LR development for an adaptation response to cold stress via signaling pathways as depicted in the model (Figure 8). A recent study showed that CRF2 and CRF6 transcriptionally control genes encoding PIN-FORMED (PIN) auxin transporters such as PIN1 and PIN7, providing a crosstalk component that fine-tunes auxin transport capacity downstream of cytokinin signaling to control plant growth and development ( Simá sková et al, 2015). Therefore, CRF2 and CRF3 gate endogenous hormone signals, such as cytokinin and auxin, as well as the environmental cold signal, providing adaptation versatility to the plants under cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Founder cells develop into lateral root primordia and lateral roots, a process modulated by other hormones, environmental signals, and developmental programs. Cytokinins create positional cues for new lateral roots, reducing lateral root formation and ensuring sufficient spacing between two neighboring lateral roots (Laplaze et al, 2007;Šimášková et al, 2015). However, the levels of root cytokinins under standard growth conditions are too high for optimal root growth, as increased root size might help the plant to absorb more water and improve nutrient acquisition.…”
mentioning
confidence: 99%